Riverine landscapes, water resource development and management: A view from downunder. (30th March 2020) - Thoms, Martin; Rose, Teresa; Dyer, Fiona
Abstract: A perfect storm refers to an event in which a rare combination of circumstances significantly exacerbates the event. River science faces a potential perfect storm through the emergence of several factors. First, pronounced and persistent human modifications to catchments and rivers have resulted in regime shifts—a state change of riverine landscapes. Anthropocene Rivers have different ecosystem structures and functions and cannot return to their "natural state." This new regime challenges accepted river science paradigms, especially those focused on traditional models of stressor—response. Second, river science is rapidly transitioning from a multidisciplinary activity focused on biophysical structures and functions, to rivers as social–ecological systems. The rise of interdisciplinary research not only recognizes the high degree of coupling between natural and human components, but also the generation of river knowledge that is more socially accountable. Third, the application of scientific knowledge to solve "wicked" river problems continues. However, increasingly river managers are faced with decisions in an environment of high uncertainty about what they are managing, and the potential impacts of their actions. The manuscripts in this Special Issue highlight a potential perfect storm facing Australian riverine landscapes. The issue is dedicated to Professor Wayne Erskine; an intellectual leader of Australian river science for over 20 years. Focussed on the science and management of Australian Rivers, the 14 manuscripts broadly cover the areas in which Wayne made his greatest contributions: river processes and management. Each has a strong foundation in theory and has application in helping to solve some of the complex problems faced by Australia's river managers across a range of spatial and temporal scales.